Pengaruh Manajemen Pelatihan dan Efektivitas Pelatihan BPSDM Kalimantan Timur Terhadap Kreativitas Mengajar Guru SMK - Dewi Nursilowati; Ucik Ana Fardila (Badan Pengembangan Sumber Daya Manusia Provinsi Kalimantan Timur, 2025)
The effectiveness of training management measurements are very important to ensure that the programs’ plan meet the needs of teachers as instructors and that it can be implemented during the Teaching and Learning Process (KBM). An appropriate training management will able to develop human resources superiority by using problem-solving abilities. It must fit the conditions that ensuring the training conducted effectively and has a positive impact on the participants work performances. This study was designed to determine the influence of training management and training effectiveness organized by the East Kalimantan Human Resource Development Agency (BPSDM of East Kalimantan). The research participants were the new vocational high school teachers of east Kalimantan. Sampling was conducted using a non-probability sampling technique quota sampling. The respondents consisted of 38 SMK teachers who had participated in competency training at BPSDM East Kalimantan. Training management implemented by BPSDM East Kalimantan was examined through three aspects: accurate training methods, quality of material content, and quality of training organizers. Meanwhile, training effectiveness was reviewed from three aspects: behavioral change, quality of training materials, and competency development. Teaching creativity was measured through five aspects: evaluation ability, the ability to explain and elaborate on problems, rational thinking, flexible thinking, and fluent thinking. This study employed an associative quantitative method. Data were processed using SPSS Version 28 through the distribution of questionnaire surveys. The results show that training management (X1) and training effectiveness (X2) organized by BPSDM East Kalimantan have an 87% influence on the teaching creativity (Y) of SMK teachers.